Atrial fibrillation and biomarkers of myocardial fibrosis in heart failure. (October 2014) - Löfsjögård, Johan; Persson, Hans; Díez, Javier; López, Begoña; González, Arantxa; Edner, Magnus; Mejhert, Märit; Kahan, Thomas
Abstract Objectives. Alterations of collagen metabolism present in heart failure promote the fibrotic substrate for the development of atrial fibrillation (AF). Myocardial collagen I synthesis and degradation can be assessed indirectly by circulating biomarkers such as the carboxy terminal propeptide (PICP) and carboxy-terminal telopeptide (CITP), respectively. Design. We examined myocardial collagen type-I metabolism in 143 patients with systolic heart failure (New York Heart Association Class 2–4) in relation to coexisting AF. Results. Mean age was 75 years, blood pressure 134/80 mm Hg, ejection fraction 34%, serum PICP 81 μg/L and CITP 8.3 μg/L, and median plasma brain natriuretic peptide 215 pg/L; 77 were in AF. PICP and CITP were related to left atrial diameter (r = 0.22, P = 0.013, and r = 0.26, P = 0.003) and CITP to pulmonary capillary wedge pressure and C-reactive protein (r = 0.19, P = 0.044, and r = 0.29, P = 0.003). A logistic regression suggested that PICP (odds ratio per 1 μg/L change 1.01, P = 0.012) and left ventricular end-diastolic volume (odds ratio per 1 mL change 0.98, P < 0.001) were independently associated with coexisting AF. Conclusion. Collagen type-I metabolism is associated to left atrial size. Heart failure patients with coexisting AF exhibit more altered collagen type-I metabolism than patients in sinus rhythm. This might represent more severe atrial and ventricular fibrosis.